2009
DOI: 10.3174/ajnr.a1740
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Infarct Core and Penumbra in Acute Stroke Using CT Perfusion Source Images

Abstract: BACKGROUND AND PURPOSE:CT perfusion (CTP) mapping has been reported to be useful in the differentiation of the infarct core and ischemic penumbra. However, the value of the CTP source imaging (CTP-SI) during the arterial and venous phases has not been fully investigated. The purpose of this study was to develop a CTP-SI methodology for acute ischemic stroke and compare its efficacy with cerebral blood flow (CBF) and cerebral blood volume (CBV) in predicting infarct core and penumbra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…21 In a recent observation comparing ASPECTS on arterial and venous phase CTP-SI with ASPECTS on cerebral blood flow and CBV, the authors observed that the penumbra region could be characterized by a mismatch between the ASPECTS on arterial phase CTP-SI and the venous phase CTP-SI. 22 This mismatch model in acute ischemic stroke could possibly determine penumbra and infarct core. 21 Baseline NIHSS is well known to predict stroke severity but may not correlate to CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…21 In a recent observation comparing ASPECTS on arterial and venous phase CTP-SI with ASPECTS on cerebral blood flow and CBV, the authors observed that the penumbra region could be characterized by a mismatch between the ASPECTS on arterial phase CTP-SI and the venous phase CTP-SI. 22 This mismatch model in acute ischemic stroke could possibly determine penumbra and infarct core. 21 Baseline NIHSS is well known to predict stroke severity but may not correlate to CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…The CS was rated as follows: ‘3’ if there complete filling of the MCA branches, ‘2’ if collateral supply filled between 50 and <100% of the occluded MCA territory, ‘1’ if collateral supply filled between 0 and <50% of the occluded MCA territory, and ‘0’ if there was the absence of collateral supply to the occluded MCA territory. We used the ASPECTS, which is a 10-point scoring system of MCA perfusion changes: a score of 10 indicates normal PCT, and a score of 0 indicates diffuse perfusion deficit throughout the territory of the MCA [7,9,17]. To assess intrarater agreement for the CBV-ASPECTS, TTP-ASPECTS, CBS and CS, intervals between the two parameters were instituted with a 1- to 2-month delay in order to avoid recall bias.…”
Section: Methodsmentioning
confidence: 99%
“…Multimodal CT (CTA-source imaging and PCT) is also more sensitive for early ischemic change than NCCT. Furthermore, the scoring systems such as the Alberta Stroke Program Early CT Score (ASPECTS), clot burden score (CBS) or collateral score (CS) have been developed to objectively analyze results of imaging studies and have been recently used in clinical practice [7,8,9,10]. Previous reports of imaging studies have indicated that the possibility of reperfusion is low due to a heavy clot burden and that the ischemic core is already subjected to severe damage to the extent that it is unable to recover [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of CTP with the Alberta Stroke Program Early CT Score (ASPECTS) 25 showed that the ASPECTS ratings on the venous phase correlated with CBV regions and those on the arterial phase with CBF. 26 Other parameters of nonviability of tissue with CBV thresholds Ͻ2 mL/100 g, CBF Ͻ20 mL/100 g/min, and MTT Ͼ8 seconds have been identified. 22 However, just as differing values for optimal threshold levels have been identified at different laboratories, more widely applicable values still require further validation.…”
Section: Purposes Of Imaging In Ais Patients Beyond 8 Hours: Predictimentioning
confidence: 99%
“…As for PDM, CTP may also be used either in conjunction with DWI or with CTP source imaging data or noncontrast head CT to identify the area of ischemic penumbra beyond that of the infarcted core. 26,30 Although CTP has the advantage over MRI of easier accessibility, the drawback is the volume of contrast required, which must be kept in mind when preparing for possible endovascular intervention and cumulative contrast dose. In addition, because abnormalities of perfusion are best appreciated by virtue of asymmetry with the opposite hemisphere, this technique is less optimal for posterior circulation pathology (although the same fallacy may also hold true for PWI).…”
Section: Purposes Of Imaging In Ais Patients Beyond 8 Hours: Predictimentioning
confidence: 99%